แนวทางการส่งเสริมความฉลาดรู้ทางการเงินของนักเรียนมัธยมศึกษาตอนปลาย: การวิเคราะห์โมเดล สมการโครงสร้างพหุระดับ - ประกายแก้ว ไกรสงคราม (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The study aimed to 1) develop the multilevel structural equation model of students financial literacy. 2) examine the empirical coherence of the multilevel structural equation model of students financial literacy. and 3) present guideline for promoting financial literacy of senior high school students. The research was divided into 2 phases. The study in phase 1 aimed to develop the multilevel structural equation model of students financial literacy. Samples of phase 1 were included 2,073 students, teachers, and school administrators using stratified random sampling technique based on their regions and school sizes. The data were collected using an online questionnaire which was developed to meet the psychometric properties. The study in phase 2 aimed to present guidelines for promoting financial literacy of senior high school students using interview with 22 students, teachers, and school administrators. Data from both of 2 phases were analyzed using descriptive statistics consisted of frequency, percentage, mean, SD, skewness, kurtosis, and correlation coefficient. The multilevel structural equation model analysis (3-level) was used to analyze the effects among variables in the study. The results revealed as follow: 1. The multilevel structural equation model of the students financial literacy divided into 3 levels consisted of student-level, classroom-level, and school-level model. The variables in student-level model consisted of family financial indoctrination, financial experiences, and students financial literacy. Family financial indoctrination had direct effect and indirect effect through financial experiences on students financial literacy. The variables in classroom-level model consisted of teachers’ financial literacy and financial learning management process. Teachers’ financial literacy affected on financial learning management process. While there was only one variable in school-level model that affected on both Teachers’ financial literacy and financial learning management process in classroom-level. In addition, financial learning management process had effect on students financial literacy. 2. The multilevel structural equation model of the students financial literacy was fitted with empirical data (chi2 = 266.25, df = 140, p = .000, CFI = 0.979, TLI = 0.972, RMSEA = 0.021). The result reveled that family financial indoctrination had direct effect on students financial literacy and financial experience as .616 and .368 respectively with a statistical significance level of .05. In addition, family financial indoctrination had an indirect effect on students financial literacy through their financial experiences as .337. In conclusion, total effect of family financial indoctrination on students financial literacy was .953. Teachers’ financial literacy had direct effect on financial learning management process as .618 with a statistical significance level of .05. Moreover, teachers financial learning management process had effect on students’ financial literacy as .467 with a statistical significance level of .05. While schools’ support for financial learning management had effect on teachers’ financial literacy as .415 with statistical significance level of .05 level. 3. Guidelines for promoting financial literacy among high school students according to the FTS Model included: 1) The family should support the financial experience. in terms of managing personal expenses to allow easy investment trials and the opportunity to conduct financial transactions via digital systems cultivate finance through financial talks and set a model for financial transactions such as savings, investments, etc. 2) Teachers conduct teaching and learning on finance by using teaching materials and learning resources online and social media. Use real financial situations to integrate with the lesson content. by designing learning management that emphasizes practice rather than theory and 3) Schools need to build strong networks of financial learning from communities and outside agencies; as well as, the schools should support teachers to develop their financial literacy that can enable them to apply financial literacy into their learning process for students’ financial literacy development.